Transmisión streaming tendencias y formatos de producción periodística - Alcívar Erazo, Josselin Nicole (2022)
The objective of this research is the multiplatform analysis and growth that transmedia journalism has forged in recent years, its representative approach is projected on the development of the Podcast as an instrument of empowerment of Freelance or independent content, which has been generated in the face of the various trendsinformative. and collective demands, of the vertiginous societies of knowledge in the face of changes and evolution of journalistic and professional work. The methodological process developed is of a mixed nature, due to the scope and investigative projection, in the same way itssample is of a stratified intentional order, taking into account the current contagion circumstances, the instruments were applied telematically, both in the techniques of survey and interview, the objectives achieved within the research allowed the authors to generate a current projection that is presented in the current transmedia profile and the resources that are generated in order of independent proposals within the framework of the podcast as an informative projection tool.